2018
DOI: 10.1242/dmm.034637
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve formation: Nos3 mutation leads to abnormal lineage patterning of neural crest cells and the second heart field

Abstract: The bicuspid aortic valve (BAV), a valve with two instead of three aortic leaflets, belongs to the most prevalent congenital heart diseases in the world, occurring in 0.5-2% of the general population. We aimed to understand how changes in early cellular contributions result in BAV formation and impact cardiovascular outflow tract development. Detailed 3D reconstructions, immunohistochemistry and morphometrics determined that, during valvulogenesis, the non-coronary leaflet separates from the parietal outflow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 53 publications
4
49
0
Order By: Relevance
“…In both mammals and birds, but not in crocodilians, a solution for the addition of the third cusp is found by adding an intercalated swelling . All these authors agree on the importance of the SHF but vary in their explanation for the development of bicuspidy by describing either a non‐anlage of intercalated cusps or a non‐disjunction from the main endocardial OFT cushion .…”
Section: Evo‐devo Aspects Of Congenital Malformationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In both mammals and birds, but not in crocodilians, a solution for the addition of the third cusp is found by adding an intercalated swelling . All these authors agree on the importance of the SHF but vary in their explanation for the development of bicuspidy by describing either a non‐anlage of intercalated cusps or a non‐disjunction from the main endocardial OFT cushion .…”
Section: Evo‐devo Aspects Of Congenital Malformationsmentioning
confidence: 99%
“…These include epicardial cells migrating from the AV junction in the case of AV cushions, and epicardial cells and NCCs in the case of OFT cushions . Each individual cushion probably receives its own balanced set of mesenchymal cells . In chicken embryos, it is shown that the formation of the semilunar valves highly depends on the interaction of endocardial and NC‐derived mesenchymal cells guided by hemodynamical forces sculpting the OFT .…”
Section: The Oft Endocardial Cushionsmentioning
confidence: 99%
See 3 more Smart Citations